2014
DOI: 10.1111/liv.12708
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary Syndrome in children: a comparative study of non‐cirrhotic vs. cirrhotic portal hypertension

Abstract: Hepatopulmonary syndrome occurs more frequently in cirrhosis, a majority being symptomatic with more severity in comparison to extrahepatic portal venous obstruction having no symptoms and less severity. There seems to be a role of liver dysfunction besides portal hypertension as an added factor in the pathogenesis of hepatopulmonary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
2
26
1
4
Order By: Relevance
“…Minimal hepatic encephalopathy occurs in about one‐third of children with EHPVO, especially those who develop spontaneous portosystemic shunts or who have surgical shunts created . Hepatopulmonary syndrome is a well‐recognized complication of EHPVO, and portopulmonary hypertension is also rarely reported . Complex multifactorial pathophysiology likely underscores other problems associated with EHPVO, including growth failure, mild disseminated intravascular coagulation (attributed to chronic subclinical endotoxemia), and portal hypertensive biliopathy .…”
Section: Natural History Of Ehpvomentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal hepatic encephalopathy occurs in about one‐third of children with EHPVO, especially those who develop spontaneous portosystemic shunts or who have surgical shunts created . Hepatopulmonary syndrome is a well‐recognized complication of EHPVO, and portopulmonary hypertension is also rarely reported . Complex multifactorial pathophysiology likely underscores other problems associated with EHPVO, including growth failure, mild disseminated intravascular coagulation (attributed to chronic subclinical endotoxemia), and portal hypertensive biliopathy .…”
Section: Natural History Of Ehpvomentioning
confidence: 99%
“…(22)(23)(24) Hepatopulmonary syndrome is a wellrecognized complication of EHPVO, and portopulmonary hypertension is also rarely reported. (25,26) Complex multifactorial pathophysiology likely under-scores other problems associated with EHPVO, including growth failure, mild disseminated intravascular coagulation (attributed to chronic subclinical endotoxemia (27) ), and portal hypertensive biliopathy. (28)(29)(30) Children with EHPVO commonly demonstrate impaired quality of life affecting all domains when measured using a standard, validated tool that assesses physical, social, scholastic functioning, and emotional domains.…”
Section: Natural History Of Ehpvomentioning
confidence: 99%
“…In the study by Sari et al, out of 16 non-cirrhotic pediatric cases, none of them fulfilled the diagnostic criteria of HPS 5. Another study of a pediatric non-cirrhotic population showed the prevalence of HPS was 13% 3. This suggests that HPS in a pediatric population with NCPF is a rare phenomenon.…”
Section: Case Reportmentioning
confidence: 96%
“…Though reported in more than one-third of cirrhotic patients, HPS is a rare entity in non-cirrhotic portal hypertension and is usually asymptomatic, especially in younger patients 2-4. Very limited pediatric data are available for HPS prevalence, especially in non-cirrhotic subjects.…”
Section: Case Reportmentioning
confidence: 99%
“…HPS is diagnosed in 4 to 47% of patients with cirrhosis and 15 to 20% of candidates for liver transplant [7][8][9]. Studies in children have shown that HPS occurs in 9 to 29% of children with chronic liver disease [10].…”
Section: Definition Prevalence and Classificationmentioning
confidence: 99%